Indirect Wave Load Estimates Using Operational Modal Analysis - Vigsø, Michael (AU Library Scholarly Publishing Services, 2020)
Wave loading of oﬀshore structures may pose a governing element to their design and drive the operational conditions. As oﬀshore structures, such as oil rigs and wind turbines, are exposed to the harsh environment at sea, they are pronetofatiguedamage,whichlimitstheiroperationallifetime. Predictingthe wave loading is subject to much uncertainty as it depends on the site-speciﬁc metocean conditions and surface properties of the structure. These conditions may change during the lifetime of the installations. It is thus of great interest to monitor the wave loading occurring at actual conditions to ensure that the reliability is maintained. This thesis features methods of indirect measurements of wave loading. Since it is unfeasible to measure the loading directly, operators need to rely on indirect methods instead. This is done by utilizing the information embedded within the vibrations of the structure. By means of output-only system identiﬁcation techniques, it is possible to decipher these vibrations to obtain an estimate of the loads. The thesis addresses the current state-of-the-art techniques for system identiﬁcation and, successively, load identiﬁcation algorithms. Solutions are evaluated in both the frequency domain as well in the time domain. The performance of load identiﬁcation is demonstrated through multiple experimental campaigns in both dry and wet conditions. It is sought to determine the limitations of the methods under diﬀerent loading conditions. Attached to this thesis are eight papers which combined span the extent of this study. Chapter6 shows the papers arranged by the suggested reading order.